(untitled) (Journal of Economics and Management Research, 2020)
ملخص: يعد دعم الغذاء إحدى وسائل شبكات الأمان الاجتماعى والتى تستهدف توفير الاحتياجات الغذاية للأسر الفقيرة. ويستلزم ترشيد نظام الدعم آليات محددة للاستهداف لضمان وصوله للفئات المستحقة. ولقياس كفاءة الاستهداف لنظام دعم السلع الغذائية ببطاقات السلع التموينية فى مصر تعتمد الدراسة على مؤشرات نسبة تسرب الدعم للفئات غير المستحقة ونسبة عدم التغطية للفئات المستحقة للدعم. ويتضح من الدراسة عدم دقة كفاءة استهداف الفقراء بنظام دعم الغذاء فى مصر، حيث تشير النتائج إلى عدم التغطية الكاملة للمستحقين من الفقراء لدعم الغذاء وتسرب نسبة كبيرة من هذا الدعم لغير الفقراء. Abstract: Food subsidy is one of the means of social safety nets that target the nutritional needs of poor families. Rationalization of the subsidy system requires specific targeting mechanisms to ensure that it reaches the eligible groups. In order to measure the targeting efficiency of the food commodity subsidy system for the food ration cards in Egypt, the study relies on indicators of the percentage of subsidy leakage for the non-deserving groups and the non-coverage ratio for the groups that are eligible for subsidy. It has been found that the targeting of the poor is not accurate in the food subsidy system in Egypt, as the results indicate the lack of full coverage of those deserving of the poor to be subsidized and a large percentage of this subsidy is leaked to the non-poor.